John Coltrane - Liebman, David (Jazz Research Journal, 2009)
This article was prepared by Peter Elsdon, with editorial assistance from Sarina Velt. This article is a transcription of the address given by saxophonist David Liebman at the International Coltrane Colloquium in Tours, France, November 2007. While it has been edited for publication, we have tried to stay as true to the spirit of Liebman’s remarks as possible. Liebman’s perspective is that of a musician growing up during the time at which Coltrane was at his creative peak. His memories of watching the Coltrane quartet play live attests to the transformative power these performances had on many young musicians around this time. Liebman also gives an insight into the conditions in which the Coltrane quartet worked, and his comments on the clubs in which the group performed (which by extension serve as a commentary on the working conditions for professional jazz musicians around this time) are particularly interesting. This emphasis on the economic realities experienced by working jazz musicians at this time serves as a useful counterbalance to the tendency in commentary on Coltrane to elevate his performances to the status of the otherworldly. Liebman also reflects on dealing with the legacy of Coltrane in his own playing, through comments which illuminate the sometimes overbearing influence forebears can exert over musicians seeking to forge their own paths.